ANALYSIS OF THE EFFECTIVENESS OF ESSAY TESTS AND OBJECTIVE TESTS IN COGNITIVE EVALUATION OF HADITH AT MA MUHARRIKUNNAJAAH - Arman Maulana Ridho (Makkah: Journal Of Islamic Studies, 2025)
Evaluation of cognitive learning outcomes in hadith instruction at madrasahs often fails to reflect students’ deep understanding, even when high scores are obtained through objective tests. This study aims to compare the effectiveness of essay tests and objective tests in measuring the cognitive abilities of Grade X students at Madrasah Aliyah Muharrikunnajaah. The research subjects consisted of 55 students (24 students from class X-A and 31 students from class X-B), selected through saturated sampling from the entire Grade X population, with characteristics of ages 15–17 years, male, and coming from a single Islamic boarding school–based institution. The study employed a quantitative comparative approach, with data collected through observation, interviews, and analysis of test documents, and data analysis conducted using descriptive statistics to compare mean scores, variability, and score distributions. The results show that essay tests are more effective in measuring deep understanding (mean scores of 86.21 in class X-A and 85.63 in class X-B), while objective tests are more efficient for uniform measurement (mean scores of 84.04 in class X-A and 82.22 in class X-B), with significant variation among students. The study concludes that a combination of both instruments is necessary for comprehensive evaluation, with practical implications for madrasah teachers in improving the quality of hadith instruction in accordance with 21st-century curriculum demands.